REPEAT BREEDER PADA SAPI BALI DI KABUPATEN PRINGSEWU - Amita Juliana; Madi Hartono; Sri Suharyati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Research on repeat breeders in Bali Cattles in Pringsewu Regency was held on December 2014 until January 2015 with 5 inseminators, 131 Bali Cattles that had been inseminated belong to 100 farmers. The purpose of this reserch are to know: 1) value repeat breeder of Bali Cattles in Pringsewu Regency, 2) the factors and magnitude factors which disturb repeat breeder of Bali Cattles in Pringsewu Regency. Data was analysis by logistic regression with SPSS (Statistics Packet for Social Science) program. The result showed that repeat breeder of Bali Cattles at Pringsewu Regency is 19,85%. Factors that affect the repeat breeder are education inseminator that negatively associated with factor value 1,466; the number of acceptors that negatively associated with factor value 0,390; old ranching that positively associated with factor value 0,067; the amount of provision of water that negatively associated with factor value 0,106; large cage that negatively associated with factor value 0,114; and sanitation stall that negatively associated with factor value 0,805.